A human co‐culture cell model incorporating microglia supports glioblastoma growth and migration, and confers resistance to cytotoxics. Issue 1 (5th December 2019) - Leite, Diana M.; Zvar Baskovic, Barbara; Civita, Prospero; Neto, Catia; Gumbleton, Mark; Pilkington, Geoffrey J.
Abstract: Despite the importance of the tumor microenvironment in regulating tumor progression, few in vitro models have been developed to understand the effects of non‐neoplastic cells and extracellular matrix (ECM) on drug resistance in glioblastoma (GBM) cells. Using CellTrace‐labeled human GBM and microglial (MG) cells, we established a 2D co‐culture including various ratios of the two cell types. Viability, proliferation, migration, and drug response assays were carried out to assess the role of MG. A 3D model was then established using a hyaluronic acid‐gelatin hydrogel to culture a mixture of GBM and MG and evaluate drug resistance. A contact co‐culture of fluorescently labeled GBM and MG demonstrated that MG cells modestly promoted tumor cell proliferation (17%‐30% increase) and greater migration of GBM cells (>1.5‐fold increase). Notably, the presence of MG elicited drug resistance even when in a low ratio (10%‐20%) relative to co‐cultured tumor cells. The protective effect of MG on GBM was greater in the 3D model (>100% survival of GBM when challenged with cytotoxics). This new 3D human model demonstrated the influence of non‐neoplastic cells and matrix on chemoresistance of GBM cells to three agents with different mechanisms of action suggesting that such sophisticated in vitro approaches may facilitate improved preclinical testing.